2015
DOI: 10.1007/s40097-015-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Green chemistry approach for the synthesis of gold nanoparticles with gum kondagogu: characterization, catalytic and antibacterial activity

Abstract: Gold nanoparticles (AuNPs) were prepared from HAuCl 4 using gum kondagogu, by adopting green synthesis, which is a simple, low cost and ecofriendly technique. The gum kondagogu (Cochlospermum gossypium) serves as both reducing agent and stabilizer. The formation of the AuNPs was identified through the change in the color of the solution from yellow to red. The synthesized AuNPs were characterized by various techniques. The green synthesized AuNPs were found to be stable in the pH range pH 2-12 and up to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 42 publications
(41 reference statements)
1
22
0
Order By: Relevance
“…Figure 1 shows the role of papaya leaf extract concentration on the formation of AuNPs, studied by microwaving the different concentrations (0.1 to 1%) of papaya leaf extract containing 1 mM of HAuCl 4 for 2 min of time. With an increase in the concentration of papaya leaf extract, there is an enhancement in the concentration of AuNPs (Reddy et al 2015b). Figure 2 shows the synthesis of nanoparticles by changing the concentration of HAuCl 4 and the reduction was studied with 1% papaya leaf extract.…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the role of papaya leaf extract concentration on the formation of AuNPs, studied by microwaving the different concentrations (0.1 to 1%) of papaya leaf extract containing 1 mM of HAuCl 4 for 2 min of time. With an increase in the concentration of papaya leaf extract, there is an enhancement in the concentration of AuNPs (Reddy et al 2015b). Figure 2 shows the synthesis of nanoparticles by changing the concentration of HAuCl 4 and the reduction was studied with 1% papaya leaf extract.…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
“…Several biological systems such as fruit extract, fungi, plants and bacteria can actively reduce metal ions to form metal nanoparticles in environmentally friendly conditions. Recently, green syntheses of gold nanoparticles by using Zizyphus mauritiana extract, palm oil mill effluent, enzymes, garlic extract, gum kondagogu and acacia nilotica are reported (Gan et al 2012;WhiteII et al 2012;Adelere and Lateef 2016;Reddy et al 2015b;Majumdar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After the addition of AgNPs, the intensity decrease was monitored using UV-Vis spectrophotometer. The electron transfer reaction was performed at different temperatures between 30 and 70 °C [36,45].…”
Section: Catalytic Activitymentioning
confidence: 99%
“…We also examined the effect of concentration of AgNO 3 for the synthesis of AgNPs by keeping the concentration of CMGK (0.5%) constant. Figure 1b clearly suggested that with increase of AgNO 3 concentration, more and more number of Ag + ions become available in the solution, which further reduced and effectively capped by CMGK molecules to produce more number of AgNPs [36,39,46,47].…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation